PENINGKATAN AKTIVITAS DAN KEMAMPUAN BERBICARA DENGAN MENGGUNAKAN METODE REPORTING DANPRESENTING SISWA KELAS IX B3 SMP NEGERI 14 PALU - NFN Masaat (Balai Bahasa Sulawesi Tengah, 2015)
The aim of the research is about how to increase the speaking ability of thestudent using Reporting and Presenting method. By using themethod, class’situation can be more active because the student are required to be active inspeaking. Teacher should encourage the student in finding the events andcooperating in the role of reporter and presenter. Teacher should encouragethe student’s creativity in doing the role of Reporting and Presenting inspeaking aspect. The method in this research would be Reporting andPresenting. These methods is effectively applied. The student become active,creative, and attractive when giving the information or the report. The result ofshows that the Reporting and Presenting methods can increase the activitiesand speaking abilities of student of class of IX B3 SMP Negeri 14 Palu. Thestudent’s average point in first cycle 76,04, while in the second cycle becomes85,44.The lower point in the reporting paper in the first cycle is 62,5 whilethehighest is 78,12. It is increasing in the second cycle. The lower becomes 81,25whilethe highest is 96,87. The point of the reporting paper’s presentation inthe first cycle have lowest 62,5 and highest point 87,5 while it is increasing inthe second cycle, the lowest point 75 and the highest is 93,75.